Pengaruh Waktu Belajar, Lingkungan.Sekolah dan Cara.Belajar Terhadap Hasil.Belajar Akuntansi Dasar Siswa Kelas X Akuntansi dan Keuangan Lembaga SMK Negeri 3 Padang - Santri Movva; Syamwil Syamwil (Jurnal Ecogen, 2020)
The aims of this article to know the Effect of Learning Time, School Env1ronment and Learn1ng Method on Basic Accounting Learning Outcomes of Class X AKL of Students SMK Negeri 3 Padang. In this research is a descriptive and associative research with a population of 98 students and 78 sample students with a proportional random sampling technique. Data were collected by documentation and questionnaires. The instrument testing uses validity and reliability tests. The prerequisite tests were performed with a normality test, a heteroscedasticity test, a multicollinearity test, and with a multiple regression analysis technique. The results showed: (1) Learning Time, School Environment and Learning Method together had a significant effect on Learning Outcomes, sig 0,000 <0.05 with a contribution of 87%. (2) Learning Times have a significant effect on Learning Outcomes, sig 0,000 <0.05. (3) School Environment has a significant influence on Learning Outcomes, sig 0,000 <0.05. (4) Learning Methods also have a signifikacant effect on Learning Outcomes, sig 0,000 <0.05.Keywords: learning time, school environment, learning method, learning outcomes